Impact of Bond Rating Changes on Stock Prices in India : Rating Agency Wise Analysis - Archana, H. N.; Jayanna, S.; Hiremath, Veerappayya (Indian Journal of Research in Capital Markets, 2015)
In this paper, we examined the impact of bond rating change announcement on the stock prices by computing the abnormal return of a security. The sample size of our study was 167 rating change announcements of four credit-rating agencies during the years 1991 to 2015. We used the event study methodology to estimate the expected return from a security. The study found average abnormal stock returns associated with the event, however, they were quite insignificant when tested with t -statistics, which revealed that credit ratings change announcements (either upgraded or downgraded news) carried a very minimal impact on the stock prices in the Indian context. The run test described that the average abnormal returns found occurred randomly.